Sociological Perspectives on Service Interaction in Culturally Sensitive Bereavement Contexts: The Role of Emotion in Behavioural Meaning-Making - Yoong, Wai Sin; et al. (European Journal of Social Science Education and Research, 2026)
This paper explores service interaction in the culturally sensitive bereavement situations using a sociological lens, which focusing on the role of emotion in behavioural meaning-making. This study will adopt Nirvana Johor, Malaysia as a case study context to examine the relations among engagement, emotional experience, and behavioural intention in a taboo service environment. Although the research has been done before on the dynamics revolving around hedonic situations, little attention is paid on high-involvement bereavement services. This conceptual paper proposes a sociologically grounded framework to understand behavioural meaning-making in bereavement service interaction focusing on sociological, service-dominant logic, relationship marketing, and experience economy. In this case, the interpretivist qualitative methodology will be used to comprehend how emotional and cultural factors influence meaning construction. It further outlines potential qualitative directions for future empirical research in culturally sensitive service environments. This research will add to the sociological and social psychological literature, by taking the discourse of emotion, engagement and consumer culture to bereavement services in Malaysia.